PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS XII MA. DARUL MUTA’ALLIMIN BATOBELLA GEGER BANGKALAN PADA MATA PELAJARAN PPKn - Kamilia, Nurul; Indriani, Dian Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of the Discovery Learning model on students' learning outcomes in the subject of Civics Education (PPKn) for Grade XII students at MA Darul Muta’allimin, Bangkalan. The background of the study highlights that conventional teaching methods—mainly lectures—fail to stimulate student engagement and understanding. This quantitative research utilized a pre-experimental design with one group pretest-posttest. Data were collected through cognitive tests administered before and after applying the Discovery Learning model. The findings show a significant increase in student learning outcomes after the implementation of the model. Statistical analysis using paired t-test confirmed a meaningful difference between pretest and posttest scores. It can be concluded that the Discovery Learning model effectively enhances students’ cognitive achievements in PPKn. This study recommends the use of student-centered learning models to foster deeper understanding and critical thinking skills in social science subjects.